2022
DOI: 10.1097/j.pain.0000000000002604
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulation of the pronociceptive effects of serotonin on female rat trigeminal sensory neurons is timing dependent and dosage dependent and requires estrogen receptor alpha

Abstract: Supplemental Digital Content is Available in the Text.Physiological low estradiol protects against serotonin-evoked orofacial pain, which is exacerbated by supraphysiological levels through estrogen receptor α. Estradiol triggers plasticity in trigeminal ganglia neuroanatomy and transcriptome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 127 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that ERs distributed widely throughout the central nervous system ( Shughrue and Merchenthaler, 2001 ). Modulation of pain by estrogen has been implicated by an overwhelming number of studies, and ERs’ effects in mediating estrogen function also have been disclosed ( Chen et al, 2021 ; Kaur et al, 2022 ). The actions of estrogen are mediated by two classical ER isoforms, ERα and ERβ ( Kumar et al, 1987 ; Gegenhuber et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ERs distributed widely throughout the central nervous system ( Shughrue and Merchenthaler, 2001 ). Modulation of pain by estrogen has been implicated by an overwhelming number of studies, and ERs’ effects in mediating estrogen function also have been disclosed ( Chen et al, 2021 ; Kaur et al, 2022 ). The actions of estrogen are mediated by two classical ER isoforms, ERα and ERβ ( Kumar et al, 1987 ; Gegenhuber et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, this study was performed only in male rats. There is strong evidence in the current literature that estrogen and its receptors play a role in the modulation and enhancement of nociceptive behavior and trigeminal neurons sensitivity in rats (Kaur et al., 2022). Since this study aimed to evaluate the effects of FKN signaling blockage in orofacial pain, the effects of estrogen could be a confusing factor for the assessed results.…”
Section: Discussionmentioning
confidence: 99%